Kristy Kowal at 20 m of Her Leg of the 4 x 100 m Medley Relay Gold Medal Race at the 1998 Perth World Championships - Rushall, B. S. (1999)
Video pictures (18 frames) and the appropriate technical/ biomechanical explanations for Kristy Kowal at 20 m of Her Leg of the 4 x 100 m Medley Relay Gold Medal Race at the 1998 Perth World Championships. Kristy Kowal's stroke is noticeably efficient. She is able to maintain her hips high and her front half flat for most of the stroke. Her kick is direct and used to the full possible extent. Her arms have a short phase of power generated more from a "butterfly" pulling action rather than a lateral lifting motion. There are many features of this stroke that would be useful for serving as a model for emulation by young swimmers.